Working the Paradox with Dorothy Smith: A Reflective Account - Butterwick, Shauna (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
In this reflective account, I revisit my geopolitical location, earlier life and career, and academic journey using the ideas of feminist theorist Dorothy Smith as an interpretive frame. Her theorizing and methodology have been transformative, particularly in relation to gaining insight into a paradox. In order to undertake community-engaged research, poorly recognized by traditional academic expectations of scholarship, I had to find a way to survive within the very institution that devalued this approach. Smith’s conceptual contributions, particularly her regard for women as subjects (not objects) and experts of their lives, encouraged me to undertake this reflection. And her theorizing of how women’s local everyday experiences are connected to complex relations of ruling have brought me new insights. While I had no direct connection with Smith, I experience her passions and ideas as a form of feminist solidarity.